Open source in Finnish software companies - Arto Seppä (The Research Institute of the Finnish Economy (ETLA), 2006)
This paper explores survey data focusing on open source software supply collected from 170 Finnish software firms using descriptive statistical analysis. The first half of the report contains general data about software companies and the differences between proprietary and open source firms. The second half focuses on open source firms. A subject of analysis are copyrights, products and services supply, the firms' relationships with the open source community, and their views on opportunities and obstacles in business. OSS firms tend to be younger and are generally smaller in terms of revenue and personnel than non-OSS firms. In addition, they display more negative attitudes towards patenting. Licensing has much less impact on their sales as compared to non-OSS firms. The majority of open source products are released under the copyleft license. Network effects are seen as biggest obstacles for successful business in the open source field.
Keywords: 330; Softwareindustrie; Urheberrecht; Deskriptive Statistik; Finnland; Open Source